A Soft Landing Approach for the Centrifugal Microgel Synthesis Process - Badalan, Matei; Adisson, Lucie; Boldron, Arthur; Achard, Jean-Luc; Ghigliotti, Giovanni; Balarac, Guillaume; Bottausci, Frédéric (Comptes Rendus. Mécanique, 2023)
Centrifugal microencapsulation has been shown to be a promising encapsulation technique, satisfying at the same time many requirements needed for biomedical applications (monodispersity, controlled size, spherical shape, sterile production environment) and allowing a high capsules production rate, using only conventional lab material. Another important advantage of this technology is the ability to process highly viscous biopolymer solutions. The usage of such solutions is desirable in multiple biomedical applications, because they yield capsules with improved mechanical properties (stiffness and yield strength) and with optimised porosity, which increases the immunoprotection in the case of biomaterial encapsulation applied to cell therapy and enhances a prolonged dissolution behaviour in the case of drug delivery applications. However, previous studies have shown that spherical capsules cannot be obtained using highly viscous solutions, and a capsule tail is always present when such solutions are used. This represents a significant limitation of this technology, since capsule shape regularity is an important requirement for various biomedical applications (e.g. cell therapy implants, drug delivery). In this article we propose and validate experimentally an adaptation of the centrifugal microencapsulation, based on the concept of “soft landing” [1]. This technique allows the production of ellipsoidal and spherical capsules using very viscous (typically up to several tens of $Pa.s$) biopolymer solutions.